Parental employment and children's academic achievement - Hannah Schildberg-Hörisch (IZA World of Labor, 2016)
Female labor market participation rates have increased substantially in many countries over the last decades, especially those of mothers with young children. This trend has triggered an intense debate about its implications for children's well-being and long-term educational outcomes. The overall effect of maternal and paternal employment on children's cognitive and educational attainment is not obvious: on the one hand, children may benefit from higher levels of family income, on the other hand, parental employment reduces the amount of time parents spend with their children.
Keywords: I21; J13; J22; 330; parental employment; parental leave; children's cognitive outcomes; educational attainment; income; parental time spent on childcare